Determination of priority pesticides in water samples combining SPE and SPME coupled to GC-MS. A case study: Suquía River basin (Argentina) - Bonansea, Rocio Ines (2013)
This study reports a combined method using solid phase extraction (SPE), followed by solid phase microextraction (SPME) to concentrate different pesticides, including chlorinated, organophosphorus, triazines, pyretroids and chloroacetamides, present at trace levels in water samples. Identification and quantification was carried out by gas chromatography coupled to Mass Spectrometry (GC-MS). The optimized methodology showed LOQs at ngL-1 levels (ranging 0.2-3.5ngL-1) in addition to acceptable precision and robustness (recoveries ranged 63-104%, RSD from 4% to 23%), presenting a novel method to reach trace levels, similar to that obtainable using EC detector, with structural confirmation by MS during the analysis of a wide range of environmental pollutants.This method was applied to the study of temporal and spatial distribution of pesticides in the Suquía River basin (Córdoba-Argentina). As expected, highest levels of agrochemicals were observed in areas with intensive agricultural practices, being atrazine (max.=433.9ngL-1), alpha-cypermetrine (max.=121.7ngL-1) and endosulfan sulfate (max.=106.7ngL-1) predominant. In urban areas, the prevalent pesticide was alpha-cypermethrine. These results draw attention to the need of pesticide monitoring programs in rivers, considering both urban and rural sections.